Persepsi Orang Tua Sebagai Determinan Utama Minat Pemanfaatan Pelayanan Kesehatan Gigi dan Mulut bagi Siswa Sekolah Dasar - Herman, Herman; Suprapto, Sentot Imam; Ellina, Agusta Dian (FORIKES, 2025)
Oral health is an essential component in maintaining children's general health, especially in elementary school-aged children. However, the utilization rate of oral health services among elementary school children in Indonesia is still relatively low, reflecting a gap between the importance of oral health and their interest in utilizing dental and oral health services. The purpose of this study was to analyze the influence of knowledge, parental perceptions, and infrastructure on the interest in utilizing dental and oral health services among parents of elementary school students in the Larat Community Health Center (Puskesmas) area, North Tanimbar District. This study used a cross-sectional design involving 329 parents of elementary school students selected using proportional random sampling. Data were collected using a questionnaire to measure knowledge, perceptions, infrastructure, and interest in utilizing dental and oral health services. Analysis was then conducted using an ordinal regression test. The results showed that the p-value for each factor was 0.004 for knowledge, 0.000 for perception, and 0.049 for infrastructure. Furthermore, it was concluded that perception, knowledge, and infrastructure are determinants of interest in utilizing dental and oral health services among parents of elementary school students.Keywords: dental and oral health; services; interest; knowledge; perception; infrastructure ABSTRAK Kesehatan gigi dan mulut merupakan komponen esensial dalam menjaga kesehatan umum anak, terutama pada anak usia sekolah dasar. Namun, tingkat pemanfaatan pelayanan kesehatan gigi dan mulut pada anak sekolah dasar di Indonesia masih relatif rendah, sehingga mencerminkan adanya kesenjangan antara pentingnya kesehatan gigi dan mulut dengan minat pemanfaatan pelayanan kesehatan gigi dan mulut. Tujuan penelitian ini adalah menganalisis pengaruh pengetahuan, persepsi orang tua dan sarana prasarana terhadap minat pemanfaatan pelayanan kesehatan gigi dan mulut pada orang tua siswa sekolah dasar di wilayah kerja Puskesmas Larat, Kecamatan Tanimbar Utara. Desain penelitian ini adalah cross-sectional yang melibatkan 329 orang tua siswa sekolah dasar yang dipilih dengan teknik proportional random sampling. Data dikumpulkan menggunakan kuesioner untuk mengukur pengetahuan, persepsi, sarana prasarana dan minat pemanfaatan pelayanan kesehatan gigi dan mulut. Selanjutnya dilakukan analisis menggunakan uji regresi ordinal. Hasil penelitian menunjukkan bahwa nilai p untuk masing-masing faktor adalah pengetahuan adalah 0,004, persepsi adalah 0,000, sedangkan sarana prasrana adalah 0,049. Selanjutnya disimpulkan bahwa persepsi, pengetahuan dan sarana prasarana merupakan determinan minat pemanfaatan pelayanan kesehatan gigi dan mulut pada orang tua siswa sekolah dasar.Kata kunci: kesehatan gigi dan mulut; pelayanan; minat; pengetahuan; persepsi; sarana prasarana